2022
DOI: 10.1007/s12010-022-04060-x
|View full text |Cite
|
Sign up to set email alerts
|

Cynaropicrin Averts the Oxidative Stress and Neuroinflammation in Ischemic/Reperfusion Injury Through the Modulation of NF-kB

Abstract: Cerebral ischemia and successive reperfusion are the prevailing cause of cerebral stroke. Currently cerebral stroke is considered to be one of the prior causes for high mortality, disability, and morbidity. Cynaropicrin, a sesquiterpene lactone, exhibits various pharmacologic properties and also has an anti-inflammatory property associated with the suppression of the key pro-inflammatory NF-κB pathway. The protective effect of cynaropicrin against oxidative stress and neuroinflammation during CIR injury throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In addition, much like endogenous antioxidant mechanisms, exogenous antioxidants function as free radical scavengers, neutralizing ROS. Numerous studies have explored the ability of antioxidants to reduce inflammation and oxidative damage by down-regulating NF-κB and elevating Nrf2 ( Li et al, 2016 ; Caglayan et al, 2019 ; Wang et al, 2021 ; Barber et al, 2023 ; Habotta et al, 2023 ; Jin and Leng, 2023 ). Nrf2 also induces expression of brain derived neurotrophic factor (BDNF), a key molecule in synaptic plasticity and learning and memory ( Tang et al, 2022 ).…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…In addition, much like endogenous antioxidant mechanisms, exogenous antioxidants function as free radical scavengers, neutralizing ROS. Numerous studies have explored the ability of antioxidants to reduce inflammation and oxidative damage by down-regulating NF-κB and elevating Nrf2 ( Li et al, 2016 ; Caglayan et al, 2019 ; Wang et al, 2021 ; Barber et al, 2023 ; Habotta et al, 2023 ; Jin and Leng, 2023 ). Nrf2 also induces expression of brain derived neurotrophic factor (BDNF), a key molecule in synaptic plasticity and learning and memory ( Tang et al, 2022 ).…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…Furthermore, this natural product has been associated with inhibiting NF-κB. Jin et al demonstrated that cynaropicrin exhibits anti-inflammatory properties by suppressing the NF-κB pathway [ 25 ]. This evidence has been reinforced by other research findings showing that cynaropicrin was able to reduce both the oxidative stress and neuroinflammation in an animal model of ischemic/reperfusion injury in a dose-dependent manner by inhibiting the NF-κB transcriptional activation pathway.…”
Section: Bioactive Compounds Extracted From C Scolymusmentioning
confidence: 99%
“…NF-κB activation is recognized as an immediate response following the onset of stroke and plays an important role in the disruption of blood-brain barrier, inflammation, and cellular apoptosis. This implies that cynaropicrin has the potential to serve as an effective therapeutic agent for cerebral ischemia-reperfusion injury [ 25 ].…”
Section: Bioactive Compounds Extracted From C Scolymusmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to these multiple specific potentials, cynaropicrin seems to be more significant and will serve towards the development of pharmaceutical substances (Elsebai et al, 2016). A recent study revealed that cynaropicrin demonstrated strong cytotoxicity on glioblastoma cells (Rotondo et al, 2022), melanoma cells (De Cicco et al, 2021), and revealed antioxidative and anti-neuroinflammatory activity in an ischemic stroke model (Jin & Leng, 2022).…”
Section: Introductionmentioning
confidence: 99%